Fungsi Rotasi Siang dan Malam dalam Al-Qur'an:Analisis Tafsir Tematik - Binti Khabibatur RA; Khamim Jazuli (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the function of the Earth’s rotation that results in the alternation of day and night from the perspective of the Qur’an using a thematic interpretative approach. Employing a descriptive qualitative method based on library research, this study relies on Qur’anic verses and Tafsir al-Misbah as primary sources, supported by scientific and astronomical literature. The findings reveal that the phenomenon of day and night in the Qur’an is not merely presented as a natural occurrence, but is understood as encompassing three interrelated functions: spiritual, theological, and pragmatic. These functions collectively reflect the Qur’anic invitation for human beings to contemplate the order of the universe as a manifestation of divine signs, thereby cultivating spiritual awareness and intellectual discernment characteristic of ulil albab.